Imitation and Drill Methods in Wanci Kahuripan Dance Learning - Adriel Brian Mahendra; Enie Wahyuning (Jurnal Pendidikan Sendratasik, 2025)
Traditional dance extracurricular programs play a strategic role in cultivating both technical dance skills and character values among students, particularly in vocational secondary schools where such programs often serve as a bridge between formal education and community-based cultural preservation. This study examines the implementation of imitation and drill methods in the learning of the Wanci Kahuripan dance within the Sekar Arum dance extracurricular program at SMKN 1 Jetis Mojokerto. The research employed a qualitative descriptive case study approach, with data collected through in-depth interviews with the extracurricular instructor, direct observation of training sessions, and documentation of student performances. The findings show that the imitation method facilitates students' initial recognition and comprehension of movement, while the drill method strengthens precision, tempo accuracy, and physical coordination through repeated practice. Continuous evaluation, combined with a personalized approach to each student, contributed to a learning atmosphere in which technical competence (wiraga) developed alongside emotional and moral internalization (wirasa) of the values embodied in the story of Mbah Semi, the legendary figure represented in the dance. The results were further evidenced by students' increasing self-confidence and their active participation in performances outside the school environment, including a regional Independence Day commemoration and a cultural exhibition opening. This study contributes to the growing body of literature on traditional dance pedagogy by demonstrating how the complementary application of behaviorist-oriented teaching methods can simultaneously support technical mastery and character education in extracurricular settings.